2014
DOI: 10.1016/j.ahj.2013.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in clinical characteristics of patients without known cardiovascular disease with a first episode of myocardial infarction

Abstract: Background Recent initiatives have focused on primary prevention to delay time to first myocardial infarction (MI). The aim of this study was to evaluate the change in risk factor profile over time in patients without known cardiovascular disease presenting with first MI. Methods In the American Heart Association's Get With The Guidelines–Coronary Artery Disease national registry, 100,884 patients without known cardiovascular disease presenting with acute MI from 408 hospitals were evaluated between 2002 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
2
9
0
1
Order By: Relevance
“…However, this cannot be the entire explanation for the increased number of observed cases of takotsubo cardiomyopathy, because after correcting for age in the multivariate model there was still a relationship between later years and increase of takotsubo cardiomyopathy in our study. Another explanation for this increase may be changed risk profiles of admitted STEMI patients over the years, which was also observed in other studies [18, 19]. These changes in risk factors only partly explain the difference in observed frequency of takotsubo cardiomyopathy in our study, since after multivariable analyses takotsubo cardiomyopathy was still more prevalent in recent years.…”
Section: Discussionsupporting
confidence: 73%
“…However, this cannot be the entire explanation for the increased number of observed cases of takotsubo cardiomyopathy, because after correcting for age in the multivariate model there was still a relationship between later years and increase of takotsubo cardiomyopathy in our study. Another explanation for this increase may be changed risk profiles of admitted STEMI patients over the years, which was also observed in other studies [18, 19]. These changes in risk factors only partly explain the difference in observed frequency of takotsubo cardiomyopathy in our study, since after multivariable analyses takotsubo cardiomyopathy was still more prevalent in recent years.…”
Section: Discussionsupporting
confidence: 73%
“…A recent study revealed modest improvements over time in risk factor profiles of patients without known cardiovascular disease who presented with a first myocardial infarction. 14 Because ventricular arrhythmias are life-threatening complications of acute myocardial infarction that are relatively common among people with no prior history of CHD, 15 documenting the incidence of CHD mortality without prior CHD diagnosis would be useful. Chugh et al 16 (p. 219) went further and mentioned that there exists ''a critical need to learn more about patients who suffer SCD…”
Section: Introductionmentioning
confidence: 99%
“…29 We report a nearly identical proportion of acutely thrombosed coronary arteries (77%) among patients with an initial shockable rhythm nearly 30 years later amongst a larger cohort; moreover, our analysis includes both witnessed and unwitnessed arrests in an era in which VF as the initial rhythm has declined in prevalence, [30][31][32][33][34][35] concomitant with a decline in overall mortality due to ischemic heart disease. 1,36 Cases that did not undergo autopsy had significantly higher rates of known risk factors for CAD than those who underwent autopsy in our cohort, which suggests that pathologically examined cases may have a lower CAD burden than their unexamined counterparts. Despite the potential for under-representation of CAD, a shockable initial rhythm was still highly predictive of acute ischemic heart disease and should be the working diagnosis until proven otherwise.…”
Section: Discussionmentioning
confidence: 91%